2019
DOI: 10.1371/journal.pone.0225817
|View full text |Cite
|
Sign up to set email alerts
|

Detrended Fluctuation Analysis in the prediction of type 2 diabetes mellitus in patients at risk: Model optimization and comparison with other metrics

Abstract: Complexity analysis of glucose time series with Detrended Fluctuation Analysis (DFA) has been proved to be useful for the prediction of type 2 diabetes mellitus (T2DM) development. We propose a modified DFA algorithm, review some of its characteristics and compare it with other metrics derived from continuous glucose monitorization in this setting. Several issues of the DFA algorithm were evaluated: (1) Time windowing: the best predictive value was obtained including all time-windows from 15 minutes to 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The pink noise may be representative of a complex movement (more flexible), the brown noise of a constrained movement, and the white noise of an incoherent movement [ 17 ]. Although the DFA can be used to analyze the time series of the CoP trajectories [ 22 ], it also has other practical applications, such as in the prediction of type 2 diabetes mellitus [ 23 ] and in the analysis of heart rate times series [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pink noise may be representative of a complex movement (more flexible), the brown noise of a constrained movement, and the white noise of an incoherent movement [ 17 ]. Although the DFA can be used to analyze the time series of the CoP trajectories [ 22 ], it also has other practical applications, such as in the prediction of type 2 diabetes mellitus [ 23 ] and in the analysis of heart rate times series [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that higher DFA was associated with worse glucose control in patients with diabetes ( 25 ). In addition, DFA was shown to be able to estimate insulin resistance either in healthy individuals or in T1DM ( 26 ), predict the probability of developing T2DM in patients at risk ( 27 ), and assess mortality in ICU patients ( 28 ). In our preliminary analysis, we found a significant difference in DFA levels between patients with LADA and T2DM, but the performance of DFA in diabetes classification was not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Colas's dataset: Colas et al 43 collected CGM data from 208 subjects with a previous diagnosis of essential hypertension and the exclusion of a previous diagnosis of diabetes mellitus or treatment with antidiabetic drugs. Patients were then followed every 6 months (6-72, median 33) until the clinical diagnosis of T2D or end of study.…”
Section: Datasetsmentioning
confidence: 99%